2017
DOI: 10.3233/jnd-170217
|View full text |Cite
|
Sign up to set email alerts
|

Improving Reproducibility of Phenotypic Assessments in the DyW Mouse Model of Laminin-α2 Related Congenital Muscular Dystrophy

Abstract: Laminin-α2 related Congenital Muscular Dystrophy (LAMA2-CMD) is a progressive muscle disease caused by partial or complete deficiency of laminin-211, a skeletal muscle extracellular matrix protein. In the last decade, basic science research has queried underlying disease mechanisms in existing LAMA2-CMD murine models and identified possible clinical targets and pharmacological interventions. Experimental rigor in preclinical studies is critical to efficiently and accurately quantify both negative and positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The respiratory function in dy W /dy W mice has also been evaluated by whole-body plethysmography. However, the breath rate did not appear to change over time and may not be predictive of pathology in dy W /dy W animals (Willmann et al, 2017). Analysis of cardiac muscle in this mouse model is required.…”
Section: Phenotype Of Dy W /Dy W Micementioning
confidence: 80%
See 3 more Smart Citations
“…The respiratory function in dy W /dy W mice has also been evaluated by whole-body plethysmography. However, the breath rate did not appear to change over time and may not be predictive of pathology in dy W /dy W animals (Willmann et al, 2017). Analysis of cardiac muscle in this mouse model is required.…”
Section: Phenotype Of Dy W /Dy W Micementioning
confidence: 80%
“…Variability in growth rates and overall survival of dy W /dy W animals from different laboratories have been noted (Willmann et al, 2017) and such discrepancies are likely to occur for the other mouse models as well. Therefore, it may be highly relevant to replicate the different therapeutic strategies in different mouse models and in different laboratories (even though such studies will be difficult to publish).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of animal models of muscular dystrophies have proven essential for a better understanding of the pathogenesis of these disorders and for developing disease-specific therapies (Saunier et al, 2016 ; Widrick et al, 2019 ). Research using mouse models for LAMA2-MD have identified potential therapeutic strategies, which, in turn, have led to improvements in murine disease pathology and survival (Miyagoe-Suzuki et al, 2000 ; Meinen et al, 2007 , 2011 ; Vishnudas and Miller, 2009 ; McKee et al, 2017 ; Reinhard et al, 2017 ; Willmann et al, 2017 ; Mohassel et al, 2018 ; Yurchenco et al, 2018 ).…”
Section: Zebrafish Models Of Muscular Dystrophiesmentioning
confidence: 99%